Place, human agency and community resilience – considerations for public health management of smoke from prescribed burning. Issue 10 (3rd October 2018) - Lyth, Anna; Spinaze, Anna; Watson, Phillipa; Johnston, Fay H.
ABSTRACT: Prescribed burning is now a widely accepted bushfire hazard management strategy. While evidence points to reduced levels of public health harm compared to severe bushfire, smoke created by planned burns remains a community concern with need for evidence-based public health management. Findings are presented from an Australian study of community experiences of prescribed burns, associated smoke, and public health communications. We find that "place" influences how information is received and used for the management of the effects of planned burns; and that this is significant for human agency and community resilience. We provide recommendations for public health management.